Effects of nanoselenium on the performance, blood indices, and milk metabolites of dairy cows during the peak lactation period - Xiao, Ming; Wang, Yajing; Wei, Manlin; Peng, Wen; Wang, Yuxiang; Zhang, Runze; Zheng, Yongjie; Ju, Ji; Dong, Chenyang; Du, Liu; Bao, Meili (Frontiers in Veterinary Science, 2024)
To compare the impact of nanoselenium and sodium selenite on the performance, blood indices, and milk metabolites of dairy cows during the peak lactation period, two groups of dairy cows under the same conditions were selected as the control group (CON group) and treatment group (NSe group) for a 38-day (10 days for adaptation and 28 days for sampling) experiment. The control group (CON) was provided a basal diet + 3.3 g/d of sodium selenite (purity1%), whereas the nanoselenium group (NSe) was offered the same diet + 10 mL/d of nanoselenium (selenium concentration 1500 mg/L). The results showed that NSe significantly increased the milk yield, milk selenium content, and feed efficiency(P<0.05), but had no significant effect on other milk components (P>0.05). NSe significantly increased blood urea nitrogen (BUN) and alkaline phosphatase (ALP)(P<0.05), but had no significant effects on malondialdehyde (MDA), superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), blood total antioxidant capacity (T-AOC), or blood selenium(P>0.05). In addition, the nontargeted metabolomics of the milk was determined by LC-MS technology, and the differentially abundant metabolites and their enrichment pathways were screened. According to these findings, NSe considerably increased the contents of cetylmannoside, undecylenoic acid, 3-hydroxypentadecanoic acid, 16-hydroxypentadecanoic acid, threonic acid, etc., but decreased the contents of galactaric acid, mesaconic acid, CDP-glucose etc. Furthermore, the enriched metabolic pathways that were screened with an impact value greater than 0.1 included metabolism of niacin and niacinamide, pyruvate, citrate cycle, riboflavin, glycerophospholipid, butanoate and tyrosine. Pearson correlation analysis also revealed a relationship between different milk metabolites and blood selenium, as well as between milk selenium and blood biochemical indices. In conclusion, compared with sodium selenite, nanoselenium improves the milk yield, feed efficiency, and milk selenium content of dairy cows and regulates milk metabolites and related metabolic pathways in Holstein dairy cows during the peak lactation period, which has certain application prospects in dairy production.